Interaction properties of solitons for a couple of nonlinear evolution equations. (January 2021) - Raza Rizvi, Syed Tahir; Bibi, Ishrat; Younis, Muhammad; Bekir, Ahmet
Abstract : We study one- and two-soliton solutions for the Cahn–Allen (CA) equation and the Brethorton equation. The CA equation has broad spectrum of applications especially in anti-phase boundary motion and it is used in phase-field models. While the Brethorton equation is a model for dispersive wave systems, it is used to find the resonant nonlinear interaction among three linear modes. We use the Hirota bilinear method to obtain one- and two-soliton solutions to the CA equation and the Brethorton equation.